Fiscal performance of minority governments: New empirical evidence for OECD countries - Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
I use new data on central and general governments for 23 OECD countries over the period 1960-2015 (unbalanced panel) to examine fiscal performance under minority governments. The results do not suggest that minority governments had higher fiscal deficits and public expenditure than majority governments - corroborating many previous studies. An innovation of my study is to examine fiscal policies of minority governments that enjoy organized support of opposition parties. The results do not show that minority governments that enjoy organized support of opposition parties increased public expenditure to a larger extent than majority governments. If anything, fiscal deficits were somewhat higher under single-party minority governments with organized support of opposition parties than under majority governments especially. Minority and majority governments had quite similar fiscal performance in OECD countries.
Keywords: D72; H00; C23; P16; 330; Minority governments; organized support of opposition parties; budgetdeficits; public expenditure; general and central government; OECD countries; paneldata models